2022
DOI: 10.1155/2022/7445398
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Deficits after an Achilles Tendon Rupture: A Narrative Review

Abstract: Persistent muscle weakness, tendon elongation, and incomplete return to preinjury level are frequent sequelae after acute Achilles tendon rupture, and evidence-based knowledge of how to best rehabilitate the injury is largely absent in the literature. The objective of this review is to illuminate and discuss to what extent an Achilles tendon rupture affects muscle, tendon, and function when assessed with the Achilles tendon total rupture score (ATRS), muscle strength, muscle cross-sectional area, tendon length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…There can be a substantial side-to-side strength deficit years after an Achilles tendon rupture, 20 which the present data corroborate (Table A5). This strength loss likely relates to the loss of muscle mass (Table 3).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There can be a substantial side-to-side strength deficit years after an Achilles tendon rupture, 20 which the present data corroborate (Table A5). This strength loss likely relates to the loss of muscle mass (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…Regardless of the initial surgical or nonsurgical approach, patients often do not recover fully from an Achilles tendon rupture. For professional athletes, a rupture of the Achilles tendon can be career ending, 23,26 and for recreational athletes, the recovery of patient-reported outcome scores is incomplete 20 and substantial functional deficits, 28 including reduced plantarflexion strength 33 and impaired heel-rise height, are reported. 44,46 The deficit in heel-rise height appears to be related to tendon length, 40,44,46 and it has been suggested that muscle fascicle length may also be a determinant of heel-rise height.…”
mentioning
confidence: 99%
“…The high-load bunch played out a profoundly serious one-sided strength preparing convention comprising of five arrangements of four plantar flexor withdrawals at 90% of isometric greatest wilful constrictions held for three seconds followed by three seconds of rest each and with 1-min in the middle between sets with the impacted leg. [21][22][23][24][25][26][27][28][29][30] This convention was executed four times each week with a portable input fitted sling which has recently been depicted. 31 The dissemination of meetings in the span of seven days was picked independently.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Following surgical repair after Achilles tendon rupture, tendon stiffness [22] and cross-sectional area (CSA) [23] are much larger even many years after surgery when compared to the non-operated side. In some cases, deficits in muscle mass, strength or function may even be permanent [24]. Hence, evidence on inter-limb asymmetries in patients suffering from Achilles tendinopathy or patients having been subjected to Achilles tendon rupture is well established.…”
Section: Introductionmentioning
confidence: 99%